VISUALIZATION OF DATASETS FROM URBAN GEOLOGY STUDIES USING GOOGLE EARTH: THE CASE STUDY OF NAFPLIO, ARGOLIS PREFECTURE. - Zananiri, I.; Zervakou, A.; Tsombos, P.; Chiotis, E. (Bulletin of the Geological Society of Greece, 2010)
The systematic use of tools provided in Geographic Information Systems in data mapping makes easy the management of the data acquired from urban geology studies. However, the information derived concern not only the scientific society but also the local authorities and the general public. Thus, a simple way of data dissemination had to be adopted. Online tools, such as those pioneered by Google EarthTM (GE), are changing the way in which scientists and the general public interact with geospatial data in a virtual environment. In the past years since its 2005 introduction, GE has introduced numerous applications, in geosciences as well as in many socio-economic disciplines. I.G.M.E., in the framework of CSF 2000 – 2006 (Operational Program “Competitiveness”), implemented the project called “Collection, codification and documentation of geothematic information for urban and suburban areas in Greece. Pilot studies”. Data management and cartographic representation was performed using G.I.S., where a geographic database was created, including all available information for the studied areas: geology, topography, satellite images, geophysical, geochemical, geotechnical, hydrogeological and geoarchaeological data. Critical information from the geodatabase concerning the study area of the city of Nafplio, Argolis Prefecture, were imported in Google Earth and stored as a Keywhole Markup Language Zipped file, rendering a 2-D layer in GE directly, to facilitate dissemination.